Conversational analysis: The relevance for health visitor clinic consultations. - Kershaw, Joan Susan (2008)
Patient Partnership Strategy (1996) and the NHS Plan (2000) formalised the notion of partnership and participation by the patient in both their own care and the delivery of services. This suggested that professionals in the NHS are not just givers of care but should be able to empower clients and involve them in the care planning. On a macro-political level, government policy is recommending that clients be involved directly with all levels of care. Traditionally, professionals working with clients have been, because of their professional status, regarded as powerful persons. In order, therefore, to achieve partnership with clients and meet government guidelines there would have to be a shift in the balance of power.